Weaving Quilts: Remaking and Reimagining Women’s Spaces and Places in Adult Literacy - Jaye Jones; Dianne Ramdeholl (Adult Education Research Conference, 2014)
In this paper two adult literacy educators critically reflect on the two programs upon which their dissertations were based. Utilizing the words of female students, they offer reflections on adult literacy pedagogical practices from a gendered, social justice perspective. Recommendations for creating more democratic adult education learning communities are also outlined.